1999
DOI: 10.1007/s001220051279
|View full text |Cite
|
Sign up to set email alerts
|

The three important traits for cooking and eating quality of rice grains are controlled by a single locus in an elite rice hybrid, Shanyou 63

Abstract: The cooking and eating quality of the rice grain is one of the most serious problems in many rice-producing areas of the world. In this study, we conducted a molecular marker-based genetic analysis of three traits, amylose content (AC), gel consistency (GC) and gelatinization temperature (GT), that are the most important constituents of the cooking and eating quality of rice grains. The materials used in the analysis included F(2) seeds, an F(2:3) population, and an F(9) recombinant inbred-line population from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
218
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(245 citation statements)
references
References 16 publications
20
218
2
5
Order By: Relevance
“…However, these traditional methods were not designed for QTL mapping; rather they were developed for analyzing the overall contribution of the genetic variance to the phenotypic variance. Traditional QTL mapping methods for diploid traits have been applied to mapping endosperm traits (Tan et al, 1999;). The assumption was that the genetic variance of an endosperm trait is controlled by the segregation of QTL in the diploid maternal plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these traditional methods were not designed for QTL mapping; rather they were developed for analyzing the overall contribution of the genetic variance to the phenotypic variance. Traditional QTL mapping methods for diploid traits have been applied to mapping endosperm traits (Tan et al, 1999;). The assumption was that the genetic variance of an endosperm trait is controlled by the segregation of QTL in the diploid maternal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Improving grain quality is one of the important objectives in cereal breeding (Sadimantara et al, 1997;Mazur et al, 1999;Tan et al, 1999;. Many grain quality traits, such as amylose content and gel consistency in rice, protein and amino-acid content in wheat, starch and gum content in barley, and sugar content in sweet corn, are endosperm traits.…”
Section: Introductionmentioning
confidence: 99%
“…Amylose content, gel consistency, and gelatinization temperature were measured according to methods reported by Tan et al (1999). Gelatinization temperature was evaluated as the alkali spreading value.…”
Section: Measurement Of Grain Quality Traitsmentioning
confidence: 99%
“…On the other hand, in introgression breeding with more distantly related lines (such as indica cultivars or wild relatives), many studies have focused on the introgression of genes related to disease and insect resistance or environmental stress tolerance, while less attention has been paid to eating quality. Several major QTLs associated with eating quality, for example, the Wx gene (Takeuchi et al 2007, Li et al 2003, Tan et al 1999) and alk region (Li et al 2003), have been reported using populations derived from crosses between a Japanese cultivar and a distantly related line or cultivar. However, it seems rather difficult to retain eating quality in introgression breeding.…”
Section: Discussionmentioning
confidence: 99%